Marriage Between the Same Clan in Pakpak Simsim Traditions Perspective of Mashlahah Mursalah - Bukti Padang; Dhiauddin Tanjung; Nispul Khair (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to describe the prohibition of marriage between clans in the Pakpak Simsim custom in the Pakpak Bharat Regency from the Mashlahah Mursaya perspective, including the causes, impacts, and influences. This study aims to: Find out how marriage between clans is in the Pakpak Simsim custom, Find out what the sanctions are for those who carry out marriage between clans in the Pakpak Simsim custom, Find out how the law of marriage between clans is in the Pakpak Simsim custom from the Mashlahah Mursalah perspective. This type of research is empirical juridical, with data collection techniques including document studies, interviews, and observations. Furthermore, the data is processed and analyzed descriptively using several theories as analytical tools such as Mashlahah Mursalah (Public Interest) and legal awareness. with the method, The results of the study provide two answers, namely: first, in the Pak-Pak community, it is very forbidden to have marriages between clans that have been in effect for generations from the ancestors, the prohibition of marriage between clans is because the Pakpak Tribe considers that one clan is a sibling who cannot be married because they are of the same sex or from the same womb. Second, according to some information, the sanctions for those who married within the same clan in the Pakpak tribe were more towards social sanctions such as being considered uncultured and against customs, not being recognized as citizens, being expelled and ostracized from the village, not being recognized as family, not adding siblings in terms of socializing, even in the past, those who married within the same clan were more cruel and sadistic, namely the couple would be killed. Third, even though in the Qur'an or hadith there is no prohibition on marriage within the same clan, there is no prohibition related to marriage within the same clan, but if viewed from the perspective of Mashlahah Mursalah there is one side of consideration that is good for maintaining the custom of prohibiting marriage within the same clan, namely maintaining kinship.